Perceived barriers to and suggested interventions for physical activity during pregnancy among participants of the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) in Southern California - Maria Koleilat; Nancy Vargas; Victoria vanTwist; Gergana Damianova Kodjebacheva (BMC, 2021)
Abstract Background The American College of Obstetricians and Gynecologists (ACOG) recommends that pregnant women engage in at least 20 to 30 min of moderate-intensity physical activity on most days of the week. Regular exercise during pregnancy is associated with many benefits for the mother and the developing fetus; yet, a large number of pregnant women do not engage in the recommended amounts. This study aimed to investigate barriers to and interventions for physical activity among pregnant WIC participants in Southern California. Methods We conducted four focus groups (FGs) with pregnant low-income women aged 18 years or older in either their second or third trimester. FGs were conducted at a WIC center in Southern California. The FGs were held according to language (English vs. Spanish-speaking) and BMI category (normal weight vs. overweight and obese). A total of 28 women participated. We used ATLAS. ti. to analyze the focus group transcripts. The study adhered to the Consolidated Criteria for Reporting Qualitative Research. Results The mean age of focus group participants was 28.9 years (SD = 6.6), and the majority were Latina. Intrapersonal barriers to physical activity were fatigue and lack of energy, pain and swelling, lack of childcare, medical restrictions and safety concerns, lack of knowledge about exercise safety, and lack of time. Interpersonal barriers included concerns and lack of support from partners and families, conflicting advice from friends and neighbors, and lack of advice on safe exercise from physicians. Women in all four groups suggested a community-based intervention where they can mingle with each other and share their challenges and concerns. Other suggestions to interventions differed among groups and reflected the women's experiences and backgrounds. Specifically, to promote education, English-speaking women preferred a brochure while Spanish-speaking women preferred a video. Overweight women emphasized including children in their exercise activities to promote healthy behavior in youth. Conclusions Interventions should be tailored to pregnant women's needs. Primary care providers should provide reassurance and information to pregnant women and their partners on the type and frequency of safe exercise.